2016
DOI: 10.4067/s0717-95022016000200058
|View full text |Cite
|
Sign up to set email alerts
|

Tribulus terrestris Hydroalcoholic Extract Administration Effects on Reproductive Parameters and Serum Level of Glucose in Diabetic Male Rats

Abstract: GHANBARI, A.; MORADI, M.; RAOOFI, A.; FALAHI, M. & SEYDI, S.Tribulus terrestris hydroalcoholic extract administration effects on reproductive parameters and serum level of glucose in diabetic male rats. Int. J. Morphol.,34(2):796-803, 2016. SUMMARY:Usage of medicinal plants for the treatment of diseases is a remarkable strategy considered in both clinical and experimental studies. This study was conducted to evaluate the effect of Tribulus terrestris hydroalcoholic extract administration on the serum level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Interestingly, treatment with the prepared NCF demonstrated significant efficiency for the reduction of testicular injury and disturbed spermatogenesis. These interpretations are in line with the growing evidence for TT, which found that the major steroidal frostanol saponin, protodioscin, encouraged spermatogenesis by stimulating the production of pituitary gonadotropins that triggered testosterone and improved sperm count by affecting Sertoli cells [ 41 ]. The presence of powerful antioxidant components like C-phycocyanin, phenolic contents, β-carotene, and vitamin C in SP were found to be mainly responsible for the antioxidant and anti-inflammatory activity through inhibition of Nf-ƙB, induction of Nrf2, maintaining the endogenous antioxidants and inhibiting the rise of testicular NO and TNF-α, thus decreasing oxidative stress and relieving the pathological changes leading to an improvement of testosterone level.…”
Section: Resultssupporting
confidence: 76%
“…Interestingly, treatment with the prepared NCF demonstrated significant efficiency for the reduction of testicular injury and disturbed spermatogenesis. These interpretations are in line with the growing evidence for TT, which found that the major steroidal frostanol saponin, protodioscin, encouraged spermatogenesis by stimulating the production of pituitary gonadotropins that triggered testosterone and improved sperm count by affecting Sertoli cells [ 41 ]. The presence of powerful antioxidant components like C-phycocyanin, phenolic contents, β-carotene, and vitamin C in SP were found to be mainly responsible for the antioxidant and anti-inflammatory activity through inhibition of Nf-ƙB, induction of Nrf2, maintaining the endogenous antioxidants and inhibiting the rise of testicular NO and TNF-α, thus decreasing oxidative stress and relieving the pathological changes leading to an improvement of testosterone level.…”
Section: Resultssupporting
confidence: 76%
“…In adult male Swiss albino mice with reproductive damage induced by cyclophosphamide, TT showed an improvement of epididymal sperm characteristics (motility) and an increase in testosterone levels as compared with the control group [65]. Extracts with TT administered to trained rats (fruit extract, China >70% saponins), diabetic rats (seed extract, Iran), healthy male rats (flowers, Iran) led to a significant increase in testosterone levels as compared with the control [66][67][68]. In healthy Wistar rats, a 70-day supplementation with TT extract influenced spermatogenesis, as shown by the changes in the tubular compartment of the testes (increase in the total tube length, tubular volume, and height of the seminiferous epithelium) [69].…”
Section: Preclinical Experimental Studies (Animal Models)mentioning
confidence: 93%
“…Studies on diabetic rats and glucose-loaded rabbits have shown that TT extracts are also capable of reducing fasting blood glucose levels, which suggests that the active compounds have multiple mechanisms of action [98][99][100]. Although the majority of the preclinical research for TT extracts was conducted on diabetic rats in order to evaluate the effect on different complications caused by diabetes, mostly related to sexual disorders, all studies reported the antihyperglycemic effect of TT extracts [67,85,86]. Diosgenin was shown to promote insulin secretion and influence beta cell regeneration in STZ-induced diabetes in rats through PPARγ activation in adipose tissue and oxidative stress modulation [101,102].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…While the majority of the preclinical research for T. terrestris extracts was conducted on diabetic rats in order to rate the different diabetes caused complications, many related to sexual disorders, all studies reported the antihyperglycemic effect of T. terrestris extracts. (Ghanbari et al, 2016;Tag et al, 2015;Zhang et al, 2019). Diosgenin (Figure 2) has been shown to promote insulin secretion and induce beta cell regeneration in STZ-induced diabetes in rats through PPARγ activation in adipose tissue and oxidative stress adjustment (Kalailingam et al, 2014;Tharaheswari et al, 2014).…”
Section: Preclinical Studiesmentioning
confidence: 99%